The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/icvts/ivw437
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap in paediatric ventricular assist device therapy with the Berlin Heart EXCOR® 15-ml pump†

Abstract: The new EXCOR 15-ml blood pump demonstrated optimal ventricular assist device support of children with a BSA of 0.33-0.5 m 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…However, that study considered eras different from those compared in our current study. In addition, improvements in the design of the Berlin Heart EXCOR were implemented from 2000 to 2012, including the addition of a 15-ml stroke volume chamber [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…However, that study considered eras different from those compared in our current study. In addition, improvements in the design of the Berlin Heart EXCOR were implemented from 2000 to 2012, including the addition of a 15-ml stroke volume chamber [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…17,18 De Rita et al found that infection of intubation site occurred in 15% of cases. 19 Only one case of poor neck incision healing occurred in our center, and no incision infection or catheter-related blood infection occurred. The main reason was that the operation was performed in a intensive care unite with laminar ow equipment, and we strictly followed aseptic surgical operations.…”
Section: Discussionmentioning
confidence: 73%
“…On the contrary, STE allows the evaluation of the function of the entire RV, following the myocardial deformation pattern of each RV segment during the entire cardiac cycle. 20 , 21…”
Section: Discussionmentioning
confidence: 99%